Chemisorption of CO2 in a gas–liquid vortex reactor: An interphase mass transfer efficiency assessment. Issue 5 (28th January 2022) - Ouyang, Yi; Nunez Manzano, Manuel; Chen, Siyuan; Wetzels, Ruben; Verspeelt, Tom; Van Geem, Kevin M.; Heynderickx, Geraldine J.
Abstract: To develop cost‐effective CO2 capture technology process intensification will play a vital role. In this work, the capabilities of a gas–liquid vortex reactor (GLVR) as novel process intensification equipment are evaluated by studying its interphase mass transfer parameters to build up the fundamentals for its future application to for example, CO2 capture. The NaOH‐CO2 chemisorption system and Danckwerts' model are applied to obtain the effective interfacial area and liquid‐side mass transfer coefficient. Results show that the gas–liquid contact in the GLVR is capable of both generating a large interfacial area in a small reactor volume and creating a region with high‐energy dissipation to improve mass transfer. A comparison of the volumetric mass transfer coefficients with data reported in literature for conventional and intensified reactor types confirms a superior mass transfer efficiency and, most importantly, a favorable energetic efficiency of the GLVR.